The Role of Mobile Applications in Enhancing the Health-Related Quality of Life of Children with Cancer: A Systematic Review and Meta-Analysis - Ana González-Díaz; Bibiana Pérez-Ardanaz; Nora Suleiman-Martos; José L. Gómez-Urquiza; Cristina Canals Garzón; Juan Gómez-Salgado (Children)
Background/Objectives: Childhood cancer, although relatively rare, has a profound impact on the quality of life of affected children and their families. Technological advances have facilitated the development of mobile applications (apps) aimed at enhancing symptom monitoring and improving communication with healthcare teams. This systematic review aimed to analyse the effect of mobile applications on the health of children with cancer, with a specific focus on health-related quality of life (HRQoL). Methods: A systematic review was conducted in accordance with PRISMA 2020 guidelines. Searches were performed in PubMed (Medline), CINAHL, Cochrane and Scopus databases using MeSH terms such as Smartphone, Mobile Applications, Child Health, Neoplasms, and Digital Health, with no date restrictions, and including studies published in English, Spanish or Portuguese. We included original research studies that examined the use of mobile apps in paediatric oncology patients. The search was completed in January 2025. Results: Of the 324 records initially identified, 14 studies (mainly pilot studies, early-phase clinical trials, and observational designs) met the inclusion criteria. Interventions commonly focused on symptom tracking (pain, nausea, fatigue), promoting treatment adherence, and delivering educational content. Several studies reported high user acceptance and a potential positive impact on HRQoL, particularly when gamification strategies were incorporated to sustain children’s engagement. Conclusions: Despite the preliminary nature and small sample sizes of most studies, mobile applications appear to be effective in supporting symptom management, communication, and health education in paediatric oncology. Their use may contribute to improvements in HRQoL. Further high-quality research involving younger children and diverse socio-cultural contexts is required to confirm their effectiveness.